Follow YOUR Heart: development of an evidence-based campaign empowering older women with HIV to participate in a large-scale cardiovascular disease prevention trial. Issue 2 (4th March 2017) - Zanni, Markella V.; Fitch, Kathleen; Rivard, Corinne; Sanchez, Laura; Douglas, Pamela S.; Grinspoon, Steven; Smeaton, Laura; Currier, Judith S.; Looby, Sara E.
Abstract : Background: Women's under-representation in HIV and cardiovascular disease (CVD) research suggests a need for novel strategies to ensure robust representation of women in HIV-associated CVD research. Objective: To elicit perspectives on CVD research participation among a community-sample of women with or at risk for HIV, and to apply acquired insights toward the development of an evidence-based campaign empowering older women with HIV to participate in a large-scale CVD prevention trial. Methods: In a community-based setting, we surveyed 40 women with or at risk for HIV about factors which might facilitate or impede engagement in CVD research. We applied insights derived from these surveys into the development of the Follow YOUR Heart campaign, educating women about HIV-associated CVD and empowering them to learn more about a multi-site HIV-associated CVD prevention trial: REPRIEVE. Results: Endorsed best methods for learning about a CVD research study included peer-to-peer communication (54%), provider communication (46%) and video-based communication (39%). Top endorsed non-monetary reasons for participating in research related to gaining information (63%) and helping others (47%). Top endorsed reasons for not participating related to lack of knowledge about studies (29%) and lack of request to participate (29%). Based on survey results, the REPRIEVE Follow YOUR Heart campaign was developed. Interwoven campaign components (print materials, video, web presence) offer provider-based information/knowledge, peer-to-peer communication, and empowerment to learn more. Campaign components reflect women's self-identified motivations for research participation – education and altruism. Conclusions: Investigation of factors influencing women's participation in HIV-associated CVD research may be usefully applied to develop evidence-based strategies for enhancing women's enrollment in disease-specific large-scale trials. If proven efficacious, such strategies may enhance conduct of large-scale research studies across disciplines.